Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1063/1.4729590
|View full text |Cite
|
Sign up to set email alerts
|

Zener tunneling between Landau orbits in two-dimensional electron Corbino rings

Abstract: Defect assistant band alignment transition from staggered to broken gap in mixed As/Sb tunnel field effect transistor heterostructure J. Appl. Phys. 112, 094312 (2012) Direct probing of density of states of reduced graphene oxides in a wide voltage range by tunneling junction Appl. Phys. Lett. 101, 183110 (2012) Comparison of tunneling current assisted by neutral and positive traps with finite ranged core-potential J. Appl. Phys. 112, 094101 (2012) Thermionic field emission in gold nitride Schottky nanodiod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…Further, the analysis by showed that heating of the 2DEG leads to additional ω π /ω c -oscillations with a phase shift with respect to the equilibrium PIRO. Separately, nonlinear mixing of PIRO and MISO in two-subband systems was shown by Bykov et al (2010a); to lead to oscillations at frequencies determined by ω π and the subband splitting energy. A further example of frequency mixing for the case of MIRO and HIRO is discussed in Sec.…”
Section: G Microscopic Theory Of Piromentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the analysis by showed that heating of the 2DEG leads to additional ω π /ω c -oscillations with a phase shift with respect to the equilibrium PIRO. Separately, nonlinear mixing of PIRO and MISO in two-subband systems was shown by Bykov et al (2010a); to lead to oscillations at frequencies determined by ω π and the subband splitting energy. A further example of frequency mixing for the case of MIRO and HIRO is discussed in Sec.…”
Section: G Microscopic Theory Of Piromentioning
confidence: 99%
“…Oscillations similar to MISO occur also in a double QW with the lowest subband states split by tunneling or, for that matter, in any other system whose energy spectrum exhibits two or more series of LLs, which are offset with respect to each other, in the presence of scattering between the series. Experimentally, MISO were studied in two-subband single QWs (Bykov et al, 2010a;Coleridge, 1990;Leadley et al, 1992Leadley et al, , 1989Rowe et al, 2001;Sander et al, 1998), in double (Bykov, 2008b;Mamani et al, 2008) and triple (Wiedmann et al, 2009b) QWs, and in wide QWs split in two layers electrostatically (Wiedmann et al, 2010a). MISO were also studied theoretically in 2D layers with electron states split by spin-orbit interaction (Langenbuch et al, 2004).…”
Section: Intersubband Magnetooscillationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a behavior is similar to the motion of quantized vortices in superfluids, for example in the nucleation of vortices at a plane boundary [8,9], with the Magnus force (analog of the Lorentz force on an electron) balancing the external force [10]. The Zener tunneling processes in the quantum Hall regime of a 2-DEG are central in the quasi-elastic inter-Landau level scattering (QUILLS) [11,12] and in the magnetoresistance oscillations in the ohmic regime [13,14]. The gyrotropic theory, however, is distinct from them in its implications for the IV-characteristics.…”
Section: Inter-landau Level Zener Tunnelingmentioning
confidence: 99%
“…Later, the Zener oscillations of the magnetoresistance r xx were found in highly doped GaAs quantum wells 2 , in double quantum wells 3 and in hole gas 4 . Very recently the Zener oscillations are detected in the differential conductance of Corbino discs, where the Hall electric field E H is absent 5 .…”
mentioning
confidence: 99%